PRICE AND VOLUME EFFECTS ASSOCIATED WITH CHANGES IN THE LQ 45 INDEX AND THE MSCI EQUITY INDEX LISTS - A.Harijono (UGM, 2003)
This paper examines price and trading volume behavior surrounding announcements of changes in the composition of the liquidity (LQ) 45 and the Morgan Stanley Capital International (MSCI) Equity Index at the Jakarta Stock Exchange. Unlike Listing studies in the developed markets, the announcements of the LQ 45 Index changes have no impact on share price and trading volume. This may be due to the samll role of Indonesiaan domestic institutional investors and purely rule-based characteristics of the LQ 45 Index. On the contrary, the markets do respond to the changes in Indonesia stocks composition of the MSCI Equity Index. it seems that global pertfolio managers, who managers, who dominate trading at the Jakarta Stock Exchange, rebalanced their portofolio when the changes in the MSCI Equity Index occured because their performances are generally benchamarks to ther return on the Index.